Investigation the performance of PV solar cells in extremely hot environments - Hassan, Mohamed K.; Alqurashi, Ibrahim M.; Salama, Ahmed E.; Mohamed, Ahmed F. (Journal of Umm Al-Qura University for Engineering and Architecture, 2022)
Manufacturers typically define photovoltaic (PV) modules under conventional test settings of 1000 W/m 2 at 25 °C, which may not be possible anywhere in the globe, because high ambient temperature is one of the most critical factors affecting photovoltaic solar cell efficiency. In this study, we will investigate the ambient temperature as well as the open circuit voltage, output power, short circuit current, and efficiency in hot regions such as Mecca (Makkah). It also discusses the correlations between PV efficiency, solar radiation, and ambient temperature. On the other hand, the addition of a layer of copper sulphate at a concentration of 1% is investigated. The use of a copper sulphate layer enhanced the PV characteristic in cases where the PV cell temperature was reduced by around (0.3–34.6 °C), while also increasing the open circuit voltage, output power, efficiency, and fill factor.